Toxic debt : an environmental justice history of Detroit - Rector, Josiah (Justice, power, and politics., 2022)
Toxic Debt is not only a book about racism, capitalism, and the making of these environmental disasters. It is also a history of Detroit's environmental justice movement, which emerged from over a century of battles over public health in the city and involved radical auto workers, ecofeminists, and working-class women fighting for clean water. Linking the histories of urban political economy, the environment, and social movements, Toxic Debt lucidly narrates the story of debt, environmental disaster, and resistance in Detroit.